Upaya dan Peran ASEAN dalam Penyelesaian Sengketa Laut China Selatan - Hermawan Bangun, Budi (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
This research examines the role of ASEAN as a regional organization, in handling South China Sea (SCS) disputes and the problems faced by ASEAN as a community in handling SCS disputes with the substance of the legal issues to be studied in this research, this research is designed as a non-doctrinal legal research which is supported by secondary data. All research results are sought to relate to one another by using deduction and induction reasoning and then the existing legal materials are analyzed qualitatively so that the conclusions are generated to provide prescriptions. In accordance The research results explain that ASEAN's role in handling SCS disputes lies in ASEAN's ability as a regional organization to try to ensure that SCS dispute resolution is carried out through diplomatic mechanisms, compliance with international law and avoiding the use of force that reflects the implementation of the